Studi Komparatif Ekuitas Merek Produk Buatan Malaysia dan Indonesia - Listiana, Erna (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The purpose of this study is to assess and obtain empirical evidence by testing different responsetowards brand equity products made in Indonesia and Malaysia. The observed product isprocessed food products biscuit, considering the existence of this Malaysia"™s processed foodproduct has a close competition with domestic processed food products. Non-probabilitysampling technique in the form of purposive sampling is applied. The study was conducted on160 respondents, consist of 80 consumers of biscuit brand made in Malaysia and 80 consumers ofbiscuit brand made in Indonesia. The study results that among Malaysia and Indonesia biscuitbrand there is a difference in case of brand association, brand loyalty and brand quality as awhole, whereas the similarity between both products is in the perceived quality.